Using Structures to Teach Legal Reasoning - Duncan Bentley (Legal Education Review)
[Extract] In 1992, The American Bar Association Task Force Report on legal education and professional development was published.1 Part of the central mission of the Task Force was to identify the skills and values required by a competent lawyer.2 Ten skills were identified. The second of these is legal analysis and reasoning.3 Legal reasoning is usually a fundamental element in the teaching and understanding of law in common law countries.4 In most core substantive law courses this takes place at least in part through a study of cases and the use of standard undergraduate problems.5 These problems are generally fairly straightforward fact patterns designed to raise one or more issues within a specific area of law. At Bond University specific structures are generally used in teaching legal reasoning. The hypothesis underlying their use is that students using such structures will improve their legal reasoning. The first part of this article describes an experiment6 to test the use by students of one such structure